Low-carbon city pilot policy, fiscal pressure, and carbon productivity: Evidence from china - Yang, Yun; Peng, Chunli (Frontiers in Environmental Science, 2022)
The implementation of the low-carbon city pilot policy is an important measure to reduce carbon emissions and promote low-carbon economic development in China. However, the resulting fiscal pressure may be counterproductive. The aim of this paper is to investigate the impacts of the low-carbon city pilot policy and fiscal pressure on carbon productivity. Based on the data of 282 cities in China over the period 2005 to 2017, this paper uses the staggered difference-in-differences (DID) model to identify the causal relationship among the low-carbon city pilot policy, fiscal pressure, and carbon productivity. The results show that this pilot policy can significantly improve carbon productivity and that the improvement effect presents a dynamic and persistent feature. However, the fiscal pressure resulting from this pilot policy can reduce carbon productivity, and the degree of reduction depends on the status of fiscal pressure. Increased fiscal pressure has a negative impact on carbon productivity, which is heterogeneous with different levels of economic development. Moreover, the mediation effect analysis finds that this pilot policy affects carbon productivity by adjusting the energy production and consumption structure, enhancing green technology innovation capabilities, and increasing the number of low-carbon-type enterprises entering the market. This paper provides new ideas for improving carbon productivity without increasing fiscal pressure. It also recommends that fiscal pressure cannot be ignored in the implementation of the low-carbon city pilot policy.